Curriculum Development and Teachers’ and Students’ Competence Improvement in The International Class Program Through Educational Collaboration - Fatchurrohman Fatchurrohman; Uktam Shamsiev Baxriddinovich (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2024)
This study aims to analyze curriculum development, strengthening teacher competencies, and students in the International Class Program (ICP) at SD Muhammadiyah Plus Salatiga through educational collaboration. This naturalistic qualitative study collected data through interviews, document study, and observation. Data were validated using technique and source triangulation. Participants were principals, managers, teaching teachers, other teachers, parents, and ICP collaborators.  Data analysis was conducted by following the interactive flow of Miles and Huberman. The results showed that the ICP of SD Muhammadiyah Plus Salatiga integrates the 2013 national curriculum and the Cambridge curriculum. The collaboration of SD Muhammadiyah Plus Salatiga with other parties is also carried out to strengthen the competence of teachers and students in the pedagogical and professional fields, and English. The novelty of the findings in this study is that strengthening teacher competence is effectively done through teacher exchange and student exchange which has not been found in previous studies. The findings of this study contribute to ICP schools strengthening and expanding collaboration with other institutions. The detailed research results will be described in this paper.